Insight into ECG: the crucial contribution of ECG technicians in cardiological monitoring and diagnosis - Shakya, Brijesh; Upadhyay, Sachin; Arshad, M. Sajid; Shadab, (International Journal of Research in Medical Sciences, 2025)
The electrocardiogram (ECG) is an indispensable non-invasive diagnostic tool which measures the heart's electrical activity and through this, very crucial in diagnosis and management of cardiovascular diseases, responsible for more than half of global deaths. Whereas advanced ECG technology is instrumental in capturing the heart activity, the expertise of ECG technicians is important for yielding precise and reliable results. This paper describes the crucial role that ECG technicians play in the healthcare system. The responsibilities include preparing patients, lead placement, operating the ECG machine, ensuring data quality control and assisting in the diagnostic process. It is their attention to detail that provides quality ECG data, which is critical in the interpretation of heart conditions, including arrhythmias, ischemia and heart attacks. More so, ECG technicians play a part in the active monitoring of patients with cardiovascular diseases or those going through treatments that influence heart health. Along with the increasing prevalence of cardiovascular conditions, there is the increase in usage of ECG technology in clinical and research settings, creating a demand for highly skilled ECG technicians. Their expertise not only enhances the accuracy of cardiovascular diagnostics but also supports advancements in medical research, helping to develop new treatments and technologies. In a nutshell, ECG technicians are vital members of the healthcare team that directly impacts patient outcomes and the future of cardiological care. Their role is crucial in ensuring that ECG remains a reliable tool for diagnosing and managing heart diseases.